A case of cluster headache treated with rotigotine: Clinical and neurophysiological correlates. (November 2013) - Di Lorenzo, Cherubino; Coppola, Gianluca; Pierelli, Francesco
Background: Chronic cluster headache (CCH) is characterized by recurrent bouts of facial pain lasting up to 180 minutes in the absence of a long remission period. Case: We report the case of a 43-year-old male patient with treatment-resistant CCH, who improved with administration of transdermal rotigotine. We also evaluated the nociceptive blink reflex habituation that was reduced before the treatment (as is usual in CH patients) and normalized by transdermal rotigotine. Conclusions: We suggest that rotigotine could represent a further therapeutic option in the treatment of drug-resistant CCH.